Synthesis and Characterization of Polyaniline/ Co\(_x\)Cr\(_{0.5}{-x}\)Fe\(_2\)O\(_4\) Nanocomposites for ElS Applications - Madhukumar, R.; Byadgi, Karabasappa H.; Renuka, C. G.; Mohan, N. R. (New Innovations in Chemistry and Biochemistry Vol. 5, 2021)
In situ polymerization was used to synthesize polyaniline (PANI)/CoxCr0.5-xFe2O4(x=0, 0.1, 0.3) nanocomposites with good electromagnetic shielding effectiveness. X-ray diffraction, Field emission scanning electron microscopy, and Vibrating sample magnetometer techniques were used to investigate PANI/ CoxCr0.5-xFe2O4(x=0, 0.1, 0.3) nanocomposites . Electromagnetic Interference (EMI) shielding effectiveness (SE) tests for PANI/ CoxCr0.5-xFe2O4(x=0, 0.1, 0.3) nanocomposites have also been carried out as a function of frequency at room temperature. Conduction mechanisms in PANI/ CoxCr0.5-xFe2O4(x=0, 0.1, 0.3) nanocomposites are in accordance with the electron hopping model. Furthermore, SE was shown to decrease as the applied frequency was increased in all generated samples. SE values for Polyaniline/CoxCr0.5-xFe2O4(x=0, 0.1, 0.3) nanocomposites rise with increasing Copper content in the composite in the current study.